Tuberculosis in pregnancy: an estimate of the global burden of disease - Jordan Sugarman, BSc; Charlotte Colvin, PhD; Allisyn C Moran, PhD; Dr. Olivia Oxlade, PhD (Elsevier, 2014)
Background: The estimated number of maternal deaths in 2013 worldwide was 289 000, a 45% reduction from 1990. Non-obstetric causes such as infectious diseases including tuberculosis now account for 28% of maternal deaths. In 2013, 3·3 million cases of tuberculosis were estimated to occur in women globally. During pregnancy, tuberculosis is associated with poor outcomes, including increased mortality in both the neonate and the pregnant woman. The aim of our study was to estimate the burden of tuberculosis disease among pregnant women, and to describe how maternal care services could be used as a platform to improve case detection. Methods: We used publicly accessible country-level estimates of the total population, distribution of the total population by age and sex, crude birth rate, estimated prevalence of active tuberculosis, and case notification data by age and sex to estimate the number of pregnant women with active tuberculosis for 217 countries. We then used indicators of health system access and tuberculosis diagnostic test performance obtained from published literature to determine how many of these cases could ultimately be detected. Findings: We estimated that 216 500 (95% uncertainty range 192 100-247 000) active tuberculosis cases existed in pregnant women globally in 2011. The greatest burdens were in the WHO African region with 89 400 cases and the WHO South East Asian region with 67 500 cases in pregnant women. Chest radiography or Xpert RIF/MTB, delivered through maternal care services, were estimated to detect as many as 114 100 and 120 300 tuberculosis cases, respectively. Interpretation: The burden of tuberculosis disease in pregnant women is substantial. Maternal care services could provide an important platform for tuberculosis detection, treatment initiation, and subsequent follow-up. Funding: United States Agency for International Development.